The effect of environmental reporting on share price among companies in Malaysia / Inayah Abdul Aziz...[et al.] - Abdul Aziz, Inayah; Awang, Moktar; Che Ali, Merani; Mohamed Zain, Mustaffa (2009)
This research is motivated by an interest in determining whether environmental reporting in the company’s annual report affects the company’s share price. The study was conducted on 16 companies listed on Main Board of Bursa Malaysia that disclosed environmental reporting. The hypothesis tested is that there is a positive association between environmental reporting with the share price of the company. The Pearson Correlation Test and Regression Analysis were used to analyze the data by comparing the share price of the company two years before and two years after the disclosure of environmental reporting in the company’s annual report. The result supports the hypothesis whereby the environmental reporting is positively associated with company’s share price.